2011
DOI: 10.1111/j.1439-0531.2011.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryopreservation on the Meiotic Spindle, Cortical Granule Distribution and Development of Rabbit Oocytes

Abstract: Although much progress has been made in oocyte cryopreservation since 1971, live offspring have only been obtained in a few species and in rabbits. The aim of our study was to evaluate the effect of vitrification and slow freezing on the meiotic spindle, cortical granule (CG) distribution and their developmental competence. Oocytes were vitrified in 16.84% ethylene glycol, 12.86% formamide, 22.3% dimethyl sulphoxide, 7% PVP and 1% of synthetic ice blockers using Cryotop as device or slow freezing in 1.5 m PROH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…While numerous reports of studies designed to investigate oocyte cryopreservation have been published in some species [64], few works have been performed in rabbit [10], [20][28] and only two recent works compared slow-freeze and vitrification methods [24], [26]. Moreover, live offspring were obtained only in one report, using the slow-freezing method [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While numerous reports of studies designed to investigate oocyte cryopreservation have been published in some species [64], few works have been performed in rabbit [10], [20][28] and only two recent works compared slow-freeze and vitrification methods [24], [26]. Moreover, live offspring were obtained only in one report, using the slow-freezing method [10].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, different technologies for in vitro development of rabbit embryos have been assayed, such as in vitro fertilisation (IVF) [31], [32], intracytoplasmic sperm injection (ICSI) [23], [33][36], and parthenogenetic activation [24], [26], [37]–[39]. Although it seems possible, IVF has not been successful in rabbit and a repeatable IVF technique has not yet been developed, possibly due to the lack of an efficient in vitro capacitation system for rabbit spermatozoa linked to the poor permeability of sperm plasma membrane [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the widespread adoption of OC technology and its marked projected growth, improving our understanding of the potential risks to the oocyte and developing embryo is imperative. Animal and human studies have demonstrated slow cooling-and vitrification-induced damage to the meiotic spindle, and data suggest that cryoprotectants may induce chromatin contraction and potentially jeopardize chromosomal competence (10). However, studies suggest that metaphase spindles repolymerize, and chromatin properly realigns postcryopreservation, and we previously reported that 96% of oocytes demonstrating a visible spindle before freezing have one after thawing (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 96%
“…The oocyte is particularly vulnerable to physical injury during the cryopreservation process, owing to its large volume and high water content, and cryopreservation causes alterations to the oocyte, including zona pellucida thickening and premature cortical granule exocytosis (4). Concerns have been raised regarding the risk of meiotic spindle disruption and aneuploidy in cryopreserved oocytes, and conflicting animal and human studies have demonstrated slow cooling-and vitrification-induced damage to the meiotic spindle (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 98%